Acetylcholine Attenuates Hydrogen Peroxide-Induced Intracellular Calcium Dyshomeostasis Through Both Muscarinic and Nicotinic Receptors in Cardiomyocytes - Palee S. (2017)
© 2016 The Author(s) Published by S. Karger AG, Basel. Background/Aims: Oxidative stress induced intracellular Ca 2+ overload plays an important role in the pathophysiology of several heart diseases. Acetylcholine (ACh) has been shown to suppress reactive oxygen species generation during oxidative stress. However, there is little information regarding the effects of ACh on the intracellular Ca 2+ regulation in the presence of oxidative stress. Therefore, we investigated the effects of ACh applied before or after hydrogen peroxide (H 2 O 2 ) treatment on the intracellular Ca 2+ regulation in isolated cardiomyocytes. Methods: Single ventricular myocytes were isolated from the male Wistar rats for the intracellular Ca 2+ transient study by a fluorimetric ratio technique. Results: H 2 O 2 significantly decreased both of intracellular Ca 2+ transient amplitude and decay rate. ACh applied before, but not after, H 2 O 2 treatment attenuated the reduction of intracellular Ca 2+ transient amplitude and decay rate. Both atropine (a muscarinic acetylcholine receptor blocker) and mecamylamine (a nicotinic acetylcholine receptor blocker) significantly decreased the protective effects of acetylcholine on the intracellular Ca 2+ regulation. Moreover, the combination of atropine and mecamylamine completely abolished the protective effects of acetylcholine on intracellular Ca 2+ transient amplitude and decay rate. Conclusion: ACh pretreatment attenuates H 2 O 2 -induced intracellular Ca 2+ dyshomeostasis through both muscarinic and nicotinic receptors.